Soft skills and learning methods for 21st-century project management: a review - Kearney, Jason (2024)
This article addresses a prominent gap in the literature by investigating the crucial soft skills required by project management students, graduates, and new practitioners entering the contemporary workforce. The literature review study adopts a concept-centric approach to examine the essential soft skills and effective learning methods for new project managers in the 21st century. Five essential 21st-century project management soft skills (communication, leadership, interpersonal, teamwork and emotional intelligence) were identified, along with three learning methods (experiential, active and reflective) that can be used to develop them. The implications of this research extend to project management students, graduates, and educators alike, emphasising the importance of nurturing the identified soft skills. As the project management domain evolves, the findings highlight the need for an education that prioritises hands-on learning and reflective practices, enabling emerging project managers to excel in their roles and drive project success.